2018
DOI: 10.1007/s13337-018-0433-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of classical swine fever virus E2 gene in cattle serum samples from cattle herds of Meghalaya

Abstract: The present study focused on the detection and genetic characterisation of 5' untranslated region (5'UTR) and E2 gene of classical swine fever virus (CSFV, family , genus) from bovine population of the northeastern region of India. A total of 134 cattle serum samples were collected from organised cattle farms and were screened for CSFV antigen with a commercial antigen capture enzyme linked immunosorbent assay (Ag-ELISA) and reverse transcription-polymerase chain reaction (RT-PCR). A total of 10 samples were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Hence, this region is highly prone to the transboundary transmission of CSFV strains. CSFV genotype 2 has been reported from outbreaks in these regions (Chakraborty et al, 2018;Patil et al, 2010;Rajkhowa, Hauhnar, Lalrohlua, Mohanarao, & J., 2014). Our isolate and the isolates of the first outbreak of CSF Moennig et al, (2003), where the CFR can reach as high as 100%.…”
Section: Discussionmentioning
confidence: 82%
“…Hence, this region is highly prone to the transboundary transmission of CSFV strains. CSFV genotype 2 has been reported from outbreaks in these regions (Chakraborty et al, 2018;Patil et al, 2010;Rajkhowa, Hauhnar, Lalrohlua, Mohanarao, & J., 2014). Our isolate and the isolates of the first outbreak of CSF Moennig et al, (2003), where the CFR can reach as high as 100%.…”
Section: Discussionmentioning
confidence: 82%
“…The sequencing of the full length E2 revealed the similarity to the CSFV 2.1 genotype. As a remarkable feature was described by this authors that the bovine samples that tested positive were mostly from farms that were in close proximity to pig farms, suggesting spillover from pigs [ 219 ], which represent a more complex situation for the control of the disease in India.…”
Section: Emergence Of New Csfv Subgenotype In Endemic Regions Undementioning
confidence: 99%
“…In another study, Bhattacharya et al [ 48 ], employing a lentivirus-based gene delivery system, constructed a stable PK-15 cell line expressing E rns (PK-E rns ) for using it to develop an ELISA detecting E rns -specific antibodies in pig sera helping in differentiation of infection from vaccinated animals. Notably, a study from the northeastern region of India reported detection of CSFV in bovine samples after screening 134 cattle serum samples using a commercial antigen capture ELISA, where 10 samples were found positive for CSFV antigen by ELISA [ 49 ].…”
Section: Csf Laboratory Diagnosis In Indiamentioning
confidence: 99%